youngTALKSyoung: Second-Generation Eduentertainment Experience on Works About Sexuality and Gender Among Teenagers - Vega Casanova, Jair; Mendivil Calderón, Carmen R. (Folios, revista de la Facultad de Comunicaciones y Filología, 2012)
The article presents the characteristics and outcome of the implementation of a second-generation eduentertainment strategy as a result of working with a group of communication, participatory production of a radio drama and peer communication strategy through conversatories on issues related to sexuality, gender and rights.Even though there are some requirements and changes in speeches, some limitations and challenges are recognized, that remain important to obtain the desired results in such processes.